Hemodynamics and Mechanobiology of Aortic Valve Inflammation and Calcification - Kartik Balachandran; Philippe Sucosky; Ajit P. Yoganathan (International Journal of Inflammation)
Cardiac valves function in a mechanically complex environment, opening and closing close to a billion times during the average human lifetime, experiencing transvalvular pressures and pulsatile and oscillatory shear stresses, as well as bending and axial stress. Although valves were originally thought to be passive pieces of tissue, recent evidence points to an intimate interplay between the hemodynamic environment and biological response of the valve. Several decades of study have been devoted to understanding these varied mechanical stimuli and how they might induce valve pathology. Here, we review efforts taken in understanding the valvular response to its mechanical milieu and key insights gained from in vitro and ex vivo whole-tissue studies in the mechanobiology of aortic valve remodeling, inflammation, and calcification.